CYP2D6 PHENOTYPES AMONG JAVANESE AND SUNDANESE SUBJECTS IN INDONESIA - UTAMI, PRI ISWATI; SUGIYANTO, SUGIYANTO; MARTONO, SUDIBYO; HAKIM, LUKMAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to determine CYP2D6 phenotype in a Javanese and Sundanese healthy subject in Indonesia. Methods: Ninety unrelated healthy Indonesian subjects from Java and Sunda were studied. Metoprolol was used as phenotyping substrate. A 100 mg oral tablet of metoprolol was administered to all the subjects. Urinary metoprolol and α-hydroxymetoprolol were determined to calculate metoprolol metabolic ratio (MR). Determination of metoprolol and α-hydroxymetoprolol was carried out by high performance liquid chromatography method. Results: Metoprolol MR varied widely (from 0.08 to 72.75). One subject (1.11%) in the study was classified as poor metabolizer (PM), one subject (1.11%) as ultrarapid metabolizer, and the remaining 88 subjects (97.78%) were classified as extensive metabolizers. Conclusion: The frequencies of PM for the CYP2D6 phenotype (1.11%) in the Javanese and Sundanese population are in concordance with most results of oxidation metabolizers in other Asian populations.